Corporate acquisition strategies and economic performance - Singh, Harbir; Montgomery, Cynthia A. (Strategic Management Journal, 1987)
This research investigates the conceptual argument that acquisitions which are related in product/market or technological terms create higher value than unrelated acquisitions. Related acquisitions are found to have greater total dollar gains than unrelated acquisitions. Acquired firms in related acquisitions have substantially higher gains than acquired firms in unrelated acquisitions. These findings indicate that related target firms benefit more from acquisition than unrelated target firms. Implications of these findings for managers are discussed.